FAKTOR-FAKTOR YANG MEMPENGARUHI HARGA SAHAM PADA PERUSAHAAN MANUFAKTUR SEKTOR PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2018-2020 - Tiara Alfinasyahri; Indrayani Indrayani; Muhammad Haykal; Mursidah Mursidah; Zainal Abidin (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis Universitas Malikussaleh, 2022)
This study aims to examine the effect of earnings per share (EPS), dividend per share (DPS), and return on assets (ROA) variables on stock prices of mining sub-sector manufacturing companies were listed on the Indonesian stock exchange in 2018-2020. The sample consisted of 11 mining companies with data published on the Indonesian stock exchange. This study uses panel data from as many as 33 observations with panel data regression estimates with a fixed-effect model assisted by the E-views 10 program. The results showed that the EPS and ROA variables did not affect stock prices while DPS affected stock prices.